Learning online : a guide to success in the virtual classroom - Lynch, Maggie McVay (Routledge study guides., 2004)
"Whether you are taking classes in school, college or university, or in a corporate training setting, it is likely that you will be expected to do at least part of your studies via the computer. This book provides realistic guidelines to ensure your success in the virtual learning environment. From detailing tools such as WebCT and Blackboard, to overcoming personal barriers to success in distance learning, this text deals with issues that readers of any age, stage or situation are likely to encounter." "The author offers anecdotes to help you avoid the pitfalls and capitalize on opportunities that will help you become a successful online student. Both current and prospective online learners will benefit from this practical book filled with detailed assistance for learning online."--Jacket